Mechanical behavior of fiber reinforced cementitious composite thin- wall cylindrical shells under internal loading uniform - S. Hosein Ghasemzadeh mosavinejad (Iranian Society of Structrual Engineering (ISSE), 2018)
With the advancement and development of the concrete industry, the construction of modern structures with high technical and economic efficiency is inevitable, that among which can be cited concrete shell structures. Concrete shell structures that often referred to as ’thin- wall shells’ are suitable structural elements for building spacious infrastructures facilities such as oil and water tanks, silos and etc. In this study, the mechanical behavior of fiber-reinforced cementitious composite thin-wall cylindrical shells under uniform hydrostatic loading has been studied. For this purpose, 36 small sized model of thin-walled cylindrical shells continuing 0%, 5%, 10% sf (partial cement replacement) and 0%, 0.5%, 1%, 1.5%, 2%, 2.5% glass fiber with w/c=0.38 were made and tested after 28 days of wet curing conditions. The compressive and flexural strengths of composite samples were tested to relating concrete strengths with the results of cylindrical shells. Results showed that, the use of silica fume has increased compressive and flexural strength up to 27% and 32%, respectively. Moreover, it also showed that the presence of fiber had no significant effect on compressive strength but increased flexural strength to 21%. In cylindrical shells the addition of sf has increased annular tensile strength to 10% and reduced a strains to28%. Furthermore, addition of 2.5% and 0.5% glass fiber has raised ultimate strain 7.4 times and annular tensile strength up to 37%, respectively.